Analisis Perubahan Kadar Fosfat, Gula Reduksi dan Brix pada Tahapan Pengolahan Nira Tebu Menggunakan Metode Asam Askorbat dan Lane–Eynon di Industri Gula - Afifah, Siti Nurul; Farida, Siti; Ferdian, Muh Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The key to maintaining the quality of the final product in the sugar industry and the efficiency of the sugar production process during granulated sugar processing is the quality control of sugarcane juice. Study aimed to chemically analyze changes in phosphate and reducing sugar levels in various types of sugarcane juice for quality control, based on operational data from a sugar factory over 10 consecutive days. Phosphate levels were analyzed using the ascorbic acid method and UV-Vis spectrophotometry and reducing sugars were analyzed using the Lane-Eynon method. The addition of phosphoric acid increased the phosphate levels of raw juice from 166.67-263.34 ppm to 206.67-306.67 ppm, indicating the effectiveness of the clarification process. However, phosphate levels decreased after treatment, which indicates process instability or excessive phosphate precipitation. Reducing sugar content was stable in early processing (1.1–2.8%) but increased to 13.53% in thick sap due to heating and evaporation. The Brix value increased during the processing stage, from 12.9–15.1% in the first-pressed sap and to 66.6–75.9% in the thick sap. An increase in the Brix value does not necessarily indicate better sap quality, as it correlates with an increase in reducing sugar content.